2020 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2020
DOI: 10.1109/cvpr42600.2020.00443
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Perspective Network for Perspective-Aware Object Counting

Abstract: One of the critical challenges of object counting is the dramatic scale variations, which is introduced by arbitrary perspectives. We propose a reverse perspective network to solve the scale variations of input images, instead of generating perspective maps to smooth final outputs. The reverse perspective network explicitly evaluates the perspective distortions, and efficiently corrects the distortions by uniformly warping the input images. Then the proposed network delivers images with similar instance scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 29 publications
0
65
0
Order By: Relevance
“…Liu et al [21] introduced a structured feature enhancement module based on conditional random fields to refine features mutually with a message passing mechanism. [22][23][24][25][26][27][28] proposed data-driven and adaptive methods that can understand highly congested scenes and perform well. Other works [29][30][31][32][33] used the multi-scale networks for image crowd counting, which are both accurate and cost-effective for practical applications.…”
Section: Map-based Methods For Crowd Countingmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [21] introduced a structured feature enhancement module based on conditional random fields to refine features mutually with a message passing mechanism. [22][23][24][25][26][27][28] proposed data-driven and adaptive methods that can understand highly congested scenes and perform well. Other works [29][30][31][32][33] used the multi-scale networks for image crowd counting, which are both accurate and cost-effective for practical applications.…”
Section: Map-based Methods For Crowd Countingmentioning
confidence: 99%
“…This dataset is mainly collected in the outside scenes, which is less intrusive and has less traffic. This paper compared with [8,22,23,34] and the experiment results show that the proposed MSR-FAN can handle this kind of simpler dataset. It can be found that the MAE value of ours is close to [34].…”
Section: Comparisons With State-of-the-artmentioning
confidence: 99%
“…CNN-based counting. With the development of deep learning [11][12][13][14], the CNN-based methods [15][16][17][18] can transform the highly congested images into the densityestimation problem. The point-level labeling is adopted to annotate the objects, and the density map is generated following the Gaussian filter [17].…”
Section: Related Workmentioning
confidence: 99%
“…For example, the Multi-column CNN (MCNN) [15] was put forward when using the cascade architecture of the CNN to regress the density map. The reverse perspective network (RPN) [16] was designed by using perspective estimators and coordinate transformers through the meta-learning for accomplishing the crowd counting task. The CODA [17] provided the alternative way which uses adversarial learning to match the predicted density map and the ground truth density map.…”
Section: Related Workmentioning
confidence: 99%
“…Some advanced methods utilize extra semantic segmentation tasks to learn crowd localization information with complicated pipelines [19,11].…”
Section: Guidance Branchmentioning
confidence: 99%